ASSESSMENT OF KNOWLEDGE AND ATTITUDE OF PEOPLE TOWARDS HIV/AIDS IN THE RURAL AREA OF NAMAKKAL DISTRICT, TAMILNADU: Pharmaceutical Science-Pharmacy Practice - KRISHNAVENI KANDASAMY; SUMITHA SELVARAJ KUMARI; SHARUMATHI SOLAIAPPAN MANOHAR; VIMALA DEVA PRASANNA GNANARAJ; SHANMUGA SUNDARAM RAJAGOPAL; SAMBATH KUMAR RAMANATHAN (International Journal of Life Science and Pharma Research, 2022)
The study was intended to assess the knowledge and attitude of people towards AIDS/HIV in a rural area. A community based cross sectional study was conducted in the rural area of Namakkal district to assess the knowledge and attitude of people. The study population included both men and women in the age group of 16-40 years; data collection was done using a semi structured pretested questionnaire, to assess the knowledge about the causes and modes of transmission of HIV / AIDS, and to assess the attitude towards people living with HIV / AIDS. Out of total 754 subjects who participated in survey, about 80% had basic knowledge on HIV. More than 90% subjects knew the modes of transmission and more than 80% are aware about prevention of HIV/AIDS. About 15% of people had misconceptions regarding transmission of the disease. Only about 20% of the study group was willing to undergo the test for HIV /AIDS. It was also found that the major source of their knowledge was from sex education in school level and media. The literacy rate of men and women were associated with their knowledge. It shows that literates (88.9%) had better knowledge than illiterates (11.1%). Basic knowledge about HIV/AIDS is lacking in this rural area. Literacy and media exposure are the factors that determine awareness of HIV among them. Here is a strong need for HIV/AIDS related education from the very beginning of childhood. This study suggests a need for education, training and awareness particularly targeting the rural youth in order to impart better knowledge and understanding on HIV/AIDS